Nutritional composition, anti-diabetic properties and identification of active compounds using UHPLC-ESI-Orbitrap-MS/MS in Mangifera odorata L. peel and seed kernel - Lasano, Nur Fatimah; Haji Hamid, Azizah; Karim, Roselina; Pak Dek, Mohd Sabri; Shukri, Radhiah; Ramli, Nurul Shazini (Multidisciplinary Digital Publishing Institute, 2019)
Mangifera odorata fruit, the hybrid forms between M. indica (mango) and M. foetida (bacang), has been shown to exhibit potential antioxidant activity, and the fruit waste could demonstrate functional and nutritional potential. In the present study, the nutritional composition (proximate, sugars, vitamins and minerals analyses), the anti-diabetic activities and phytochemical profile of M. odorata peel and seed kernel were investigated for the first time. The results indicated that seed kernel rich in fat, protein, carbohydrate, and ash while peel contained significantly greater amount of fiber, minerals, β-Carotene and ascorbic acid compared to seed kernel. The samples were then extracted using different solvents (acetone, ethanol, methanol at 60%, v/v and pure deionized water) and their anti-diabetic activities (α-amylase and α-glucosidase inhibition assay) were determined. Seed kernel had the lowest IC50 values for α-amylase and α-glucosidase inhibition assay in 60% ethanol and 60% acetone, respectively. Due to the toxic effect and high volatility of acetone, the ethanolic extracts of samples were further analyses for their phytochemical profile using high performance liquid chromatography-mass spectrometry (LC-MS) and ultra-high-performance liquid chromatography electrospray ionization orbitrap tandem mass spectrometry (UHPLC-ESI-Orbitrap-MS/MS). The most abundant compounds identified were phenolic acid, ellagic acid, and flavonoid. These findings suggest that M. odorata fruit wastes, especially the seed kernel possesses promising ability to be used as functional ingredient in the food industry.